Seeing the Seeing the Seeing: Understanding the Spectatorship of Forced Entertainment (American & British Studies Annual, 2011)
The present paper aims to explore the crucial role of the audience in the artistic strategies of Forced Entertainment, a leading contemporary British experimental theatre troupe.  The paper attempts to highlight the shift of the role of audience towards the spectator as a witness, raising thus further ethical issues. Furthermore, the company´s insistence on the presence, realness and “failure” framed by the tools of postdramatic theory and the umbrella of Live Art create a new reading of the endless interplay between the theatre and its audiences, which is illustrated on two recent performances of Forced Entertainment, Showtime (1996) and Spectacular (2008).
Keywords: Forced Entertainment; Live Art; postdramatic theatre; contemporary British experimental theatre; ethics of spectatorship; Spectacular; Showtime